1990
DOI: 10.1246/bcsj.63.2288
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Aqueous Resins. I. Water-Dispersed Polyesters Containing Polar Groups

Abstract: Water-borne polyesters which can provide a flexible film having a high resistance to water have been designed. Such hydrophobic polyesters can be dispersed into water by introducing small amounts of hydrophilic groups. When a few mol% of sodium 5-sulfonatoisophthalic acid is used as a hydrophilic group and some water-soluble organic compounds, such as 2-butoxyethanol, are used as additives, stable aqueous dispersions of polyester resins are obtained, having a fine particle size under 1.0 μm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…These modified polymers can readily be dispersed into water under low shear stress with little or no external emulsifiers. Examples of polymer latices produced in this way include hydrophilically modified epoxy resins [4], water-borne polyesters [6], and polyurethane ionomers dispersions [7].…”
Section: Introductionmentioning
confidence: 99%
“…These modified polymers can readily be dispersed into water under low shear stress with little or no external emulsifiers. Examples of polymer latices produced in this way include hydrophilically modified epoxy resins [4], water-borne polyesters [6], and polyurethane ionomers dispersions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic interactions. The main drawback of the soft interaction potential in eqn (11) is that it permits overlaps between charged beads, which may induce artificially strong ion pairing and cause a divergence in electrostatic potential. To circumvent this problem, Groot 38 coupled all beads to the local electrostatic field with the long-range part of the potential solved separately on the optimized grid.…”
Section: Dpd Platformmentioning
confidence: 99%
“…8 In their study of water-borne polyesters Kotera and Takahashi 11 confirmed the importance of hydrophilic groups in the polymer backbone to the onset of dispersion. Depending on the type of cosolvents used, the resin concentration, and the content of the SO 3 Na groups, Kotera and Takahashi 11 reported the mean particle sizes to be in the 5-75 nm range. The introduction of trace amounts of water in a low dielectric medium prolongs the counterion relaxation times, hinders the formation of ionic multiplets, and triggers the microphase separation.…”
Section: Introductionmentioning
confidence: 99%
“…7 The main hydrophilic component of the polyester resin is the alkali 5-sulfo-3,5-isophathalate moiety, and depending on its concentration, can render the resin from fully soluble in water or as colloids ranging from nano to micro size dispersions. 8 The most common alkali is the monovalent sodium, potassium, or lithium ion, but the divalent magnesium (Mg 2+ ), zinc (Zn 2+ ), calcium (Ca 2+ ) or multivalent iron (Fe 3+ ) can also be utilized to obtain larger sized dispersions. The term "waterborne" is often used interchangeably with other descriptors such as water-dissipatable, -dispersible ordispellable.…”
Section: Introductionmentioning
confidence: 99%